Subunit b-Dimer of the Escherichia coli ATP Synthase Can Form Left-Handed Coiled-Coils - Wise, John G. (The Biophysical Society, 2008)
One remaining challenge to our understanding of the ATP synthase concerns the dimeric coiled-coil stator subunit b of bacterial synthases. The subunit b-dimer has been implicated in important protein interactions that appear necessary for energy conservation and that may be instrumental in energy conservation during rotary catalysis by the synthase. Understanding the stator structure and its interactions with the rest of the enzyme is crucial to the understanding of the overall catalytic mechanism. Controversy exists on whether subunit b adopts a classic left-handed or a presumed right-handed dimeric coiled-coil and whether or not staggered pairing between nonhomologous residues in the homodimer is required for intersubunit packing. In this study we generated molecular models of the Escherichia coli subunit b-dimer that were based on the well-established heptad-repeat packing exhibited by left-handed, dimeric coiled-coils by employing simulated annealing protocols with structural restraints collected from known structures. In addition, we attempted to create hypothetical right-handed coiled-coil models and left- and right-handed models with staggered packing in the coiled-coil domains. Our analyses suggest that the available structural and biochemical evidence for subunit b can be accommodated by classic left-handed, dimeric coiled-coil quaternary structures.